Transformasi Website Crowdfunding: Pendekatan Kansei Engineering Berorientasi pada Preferensi Pengguna - Endra Abdul Hadi (CV. ULIL ALBAB CORP, 2024)
One of the crucial factors in redesigning the Sedekah Online website to provide the best experience for visitors is user involvement in the interface improvement process. This study evaluates the website using the User Experience Questionnaire (UEQ) and improves its appearance through the Kansei Engineering method to better understand user preferences. The design selection process is carried out by combining the AHP and TOPSIS methods, while data from the questionnaire are analyzed using multivariate statistical techniques. By involving users in the interface design, the final result is more in line with their expectations, which increases comfort and satisfaction when accessing the website.